Instaclop (Clopidogrel) – as a Safe Anti - Platelet Therapy - Sharipova Elvina Midatovna (Journal of Science in Medicine and Life, 2024)
The article describes the effectiveness and clinical pharmacology of the main class of modern antiplatelet agents used in the clinical practice of a cardiotherapist, intervention cardiologist in the treatment of coronary heart disease and other pathologies of the cardiovascular system. According to the latest studies conducted on the effectiveness of the drug clopidogrel (Instaclop), the main clinical and pharmacological characteristics of the drug Instaclop.